Metal dimers embedded vertically in defect-graphene as gas sensors: a first-principles study. Issue 17 (19th April 2022) - Yu, Linke; Li, Fengyu
Abstract : Unprecedented metal dimers embedded symmetrically and vertically in defect-graphene were revealed to be promising gas sensors. Abstract : A highly symmetric structure of metal dimers embedded in defect-graphene (M2 ⊥gra) in a perpendicular manner was designed. Five M2 ⊥gra (M = Co, Ni, Rh, Ir and Pt) monolayers were identified to be stable by density functional theory (DFT) calculations. To investigate the capability of those new structures as gas sensors, the adsorption behavior of ten gas molecules (O2, N2, CO, CO2, NO, NO2, NH3, H2 O, H2 S and SO2 ) on M2 ⊥gra was explored, and the charge transfer, magnetism changes, etc. of these adsorption systems were analyzed. The Ni2 ⊥gra can be used as a gas sensor for O2 at 500 K by the analysis of electronic and magnetic properties. At room temperature, the Pt2 ⊥gra is expected to be an excellent CO2 gas selector due to its high selectivity, sensitivity and short recovery time (1.04 × 10 −12 s). The electronic and magnetic coupling between the metal atoms in the vertical metal dimers plays an important role in sensing gas molecules. Our work paves a new way to design metal-dimer-based nanomaterials.